Usability component for medical consultation web-based system - A’bas, Nurul Najihah (2023)
Medical technology relies heavily on computerised technologies to offer solutions for the best possible medical management. One of the crucial medical systems is the consultation system, a digitalised tool for connecting with a specialist and asking for guidance on an electronic platform. The system usability is influenced by the effectiveness, efficiency, and satisfaction with which specific users can execute a particular set of tasks in each context. Health information technology's poor usability is still a serious challenge. Currently, the evaluation of a computerised system's usability is based on general usability principles, regardless of the delivery platform and field. The current medical usability concepts are used in the evaluation of medical computerised systems. Because of this, the current usability evaluation does not accurately reflect the system's output, leading to the creation of unpromising systems. The system created are not fully met of medical expectations and best practises in many ways. As a consequence, this study intends to thoroughly examine the necessary evaluation factors of the usability of web-based systems, focusing on the medical consultation system from the views of medical experts. The research project being presented has two stages. First, the thesis seeks to present the establishment of a new consultation system for screening for diabetic retinopathy. The evaluation of the developed system based on its general and usability components will be presented in the thesis' second section. The study develops a new set of components that serve as a fundamental for the usability of web-based systems by consolidating a critical viewpoint that is medical for producing and evaluating the usability of medical consultation systems. To meet the expected usability quality of computerised systems in the medical field, the usability evaluation components are crucial as a benchmark and guidance. This research is expected to speed up the development of computerised systems, in particular the medical consultation system, and enable the support systems to work more effectively in raising the standard of the healthcare system while also fulfilling expectations from a medical standpoint.